Implementation of the Pteridophyta Smart Card to Increase Students' Understanding of Fern Material - Atiqoh; Efendi, Wawan Wahyudi; Prihanta, Wahyu (Universitas Pendidikan Ganesha, 2024)
Ferns (Pteridophyta) are one of the materials that must be studied by biology and biology education students. However, based on previous research, many students still have difficulty recognizing or identifying ferns. This condition is caused by learning which is still carried out conventionally, relying on textbooks with minimal pictures or photos and is not in accordance with the characteristics or learning styles of current Generation Z students. Therefore, the aim of this research is to analyze the effectiveness and attractiveness of the Pteridophyta Smart Card as a learning medium to improve learning outcomes. This type of research is quantitative research using a One-Group Pretest-Posttest design with the research subjects being 20 4th semester students of the biology education study program who were selected using purposive sampling. Data collection was carried out using pretest and posttest, questionnaires and observations. The data was analyzed using an effectiveness test which was analyzed using the gain score formula, and an attractiveness test which was analyzed using a user validation calculation formula. The results of this research reveal that the Pteridophyta Smart Card media is effectively used as a learning medium for students with an attractiveness level of up to 91.25%, which means it can be concluded that the Pteridophyta Smart Card media is very attractive for students because it suits the characteristics or learning styles of Generation Z students. , so that it can improve students' learning outcomes. This research provides theoretical and practical implications in terms of improving students' learning outcomes using Pteridophyta Smart Card media.